Stimulating smallholder dairy market and livestock feed improvements through local innovation platforms in the Himalayan foothills of India - Ravichandran, Thanammal; Teufel, Nils; Capezzone, Filippo; Birner, Regina; Duncan, Alan J. (Elsevier, 2020)
Innovation platforms (IP) are increasingly used in agricultural development to address complex issues which require diverse actors to work jointly to identify constraints and implement solutions. Documenting outcomes associated with the use of IPs and identifying factors linked to positive results are important if performance is to be optimized. This study investigates changes in smallholder dairy production and marketing associated with the establishment of a series of innovation platforms in Uttarakhand, Northern Himalayan region, India. We studied the links between innovation platform processes and outcomes using systematic documentation of meetings and interventions along with a post-intervention assessment which compared households from villages with and without the innovation platform intervention. We found that households participating in IPs showed increased dairy milk sales, increased income and improved breeding and feeding practices. Factors associated with these outcomes were the process of issue identification, the diversity of actors participating in meetings and the quality of follow-up on the agreed action plans.